Flow cytometry evaluation of acrosome integrity of alpaca spermatozoa in fresh unfixed samples (0 hours) and samples fixed in formaldehyde (24 hours and 1 week) - Delgado Ordinola, Josselyn (2024)
The aim of the study was to determine the acrosome integrity (AI) in alpaca epididymal spermatozoa, both fresh unfixed and fixed with 2% formaldehyde, using the flow cytometry technique with FITC-PSA as fluorochrome. Epididymal sperm were obtained from 26 testes and grouped into 0-hour, 24-hour and 1-week samples. The samples were incubated with FITC-PSA (concentration 2.5 µg/mL). The 24-hour and 1-week samples were kept refrigerated for the corresponding time. For evaluation, formaldehyde was removed by washing with PBS. Sperm without green fluorescence were considered to have an intact acrosome. The results showed that the AI percentages were 95.89 ± 4.35% (0 hours), 97.24 ± 3.36% (24 hours) and 97.21 ± 3.49% (1 week). Pearson correlation between unfixed samples with samples fixed for 24 hours and 1 week showed strong and positive correlations (r=0.86 and r=0.84, respectively). Graph analysis showed that most of the results were in line with the established limits. In conclusion, AI in fresh unfixed sperm (0 hours) is comparable to that of samples preserved for 24 hours and 1 week using formaldehyde.